2013
DOI: 10.1073/pnas.1306371110
|View full text |Cite
|
Sign up to set email alerts
|

Reducing deformation anisotropy to achieve ultrahigh strength and ductility in Mg at the nanoscale

Abstract: In mechanical deformation of crystalline materials, the critical resolved shear stress (CRSS; τ CRSS ) is the stress required to initiate movement of dislocations on a specific plane. In plastically anisotropic materials, such as Mg, τ CRSS for different slip systems differs greatly, leading to relatively poor ductility and formability. However, τ CRSS for all slip systems increases as the physical dimension of the sample decreases to approach eventually the ideal shear stresses of a material, which are much l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(49 citation statements)
references
References 37 publications
5
42
2
Order By: Relevance
“…For the case of Wang et al [22], atomistic simulations are used to bridge these length scales, but experimental validation of such simulations has not been presented. Additionally, studies that observed the nanoscale boundary structure of materials [30,31] have been limited, and have not explored the microstructural features unique to twin interactions. in situ TEM observations have been used to study microstructure in magnesium [25,[30][31][32][33] and magnesium alloys [31,34].…”
Section: Introductionmentioning
confidence: 99%
“…For the case of Wang et al [22], atomistic simulations are used to bridge these length scales, but experimental validation of such simulations has not been presented. Additionally, studies that observed the nanoscale boundary structure of materials [30,31] have been limited, and have not explored the microstructural features unique to twin interactions. in situ TEM observations have been used to study microstructure in magnesium [25,[30][31][32][33] and magnesium alloys [31,34].…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, studies via TEM, in-situ TEM, and slip trace analyses have provided evidence in support of both types. [11,40,41] It remains to be seen whether texture calculations via crystal plasticity simulations can distinguish between the two. For the present simulations, we have elected to use pyramidal type II.…”
Section: Modeling Resultsmentioning
confidence: 99%
“…[25]. recent experiment and MD simulation have shown the importance of 〈c + a〉 dislocation in reducing anisotropic plastic deformation and thus achieve super strength and ductility [26]. However, the complexity of HCP deformation behaviour [27] has not been well understood.…”
Section: Discussionmentioning
confidence: 99%